2013
DOI: 10.1371/journal.pone.0060224
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Physiology and Ecology of the Brackish-Water-Adapted Cyanobacterium Nodularia spumigena CCY9414 Based on a Genome-Transcriptome Analysis

Abstract: Nodularia spumigena is a filamentous diazotrophic cyanobacterium that dominates the annual late summer cyanobacterial blooms in the Baltic Sea. But N. spumigena also is common in brackish water bodies worldwide, suggesting special adaptation allowing it to thrive at moderate salinities. A draft genome analysis of N. spumigena sp. CCY9414 yielded a single scaffold of 5,462,271 nucleotides in length on which genes for 5,294 proteins were annotated. A subsequent strand-specific transcriptome analysis identified m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 162 publications
(193 reference statements)
3
71
1
4
Order By: Relevance
“…Hypothetical proteins and proteins with unknown function are widely abundant among cyanobacterial genome annotations, representing the relatively incomplete knowledge of the metabolism and molecular structure of cyanobacteria (13,27). In this study, we found 5 (5hNP), 11 (6dNP), and 19 (4dLP) proteins with unknown function with more than 4-fold transcriptional changes compared with the controls (log 2 FC Ͼ2 or ϽϪ2; P Յ 0.05).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Hypothetical proteins and proteins with unknown function are widely abundant among cyanobacterial genome annotations, representing the relatively incomplete knowledge of the metabolism and molecular structure of cyanobacteria (13,27). In this study, we found 5 (5hNP), 11 (6dNP), and 19 (4dLP) proteins with unknown function with more than 4-fold transcriptional changes compared with the controls (log 2 FC Ͼ2 or ϽϪ2; P Յ 0.05).…”
Section: Resultsmentioning
confidence: 57%
“…Intergenic regions may give rise to sRNAs, another type of important regulatory factors with an important role in physiological adaption and as a driver of interstrain divergence in bacteria, including cyanobacteria (33,34,(49)(50)(51). Studies of the filamentous and nitrogen-fixing cyanobacterium Nodularia spumigena CCY9414 genome and its acclimation to stress conditions point further sRNAs crucial role in cell functioning, especially in gene expression regulation (13,52). Due to their importance as regulatory factors, we searched intergenic regions differentially expressed under phosphorus deprivation conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCC 7119; Porchia & Salerno 1996) and has been discussed as the main reason restricting these cyanobacteria to freshwater and brackish water conditions (Hagemann 2011). The genome of Nodularia CCY9414 also harbors genes for the synthesis of trehalose by the TreYZ pathway (Voß et al 2013). However, we never detected trehalose in cell extracts of salt-treated Nodularia CCY9414.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we used the Baltic Sea isolate N. spumigena CCY9414 (hereafter Nodularia CCY9414), taking advantage of its known genome sequence (GenBank accession no. AAVW 00000000; Voß et al 2013). Genome searches revealed that Nodularia CCY9414 is potentially able to synthesize sucrose as well as trehalose as compatible solutes.…”
Section: Abstract: Compatible Solute · Glutamate · Potassium · Sucrosementioning
confidence: 99%